Intraempreendedorismo no ambiente de uma clínica médica na cidade de Mossoró-RN - Nogueira, Igor Flávio Freire (Universidade Federal Rural do Semi-Árido, 2017)
The intraempreendedor behavior is increasingly being valued by organizations once that corresponds to the position of the employee who seeks to find new opportunities to implement improvements in processes, productsor services of the organization, in other words, is creative, innovative, flexible and goes beyond what is requested. In this sense the objective of this work was to general analyze ifthe management contributes to the development of intrapreneurshipinthe organizational environment. To respond to this goal, were proposed three specific objectives: check what are the main challenges for intrapreneursin the corporate environment;identify the profile of respondents and check if the organization adopts a culture geared to intraempreendedorismo. The survey was conducted in a medical clinic in the city of Mossoro-RN, by means of a qualitative approach, exploratory and descriptive case study. For data collection it was used as a tool a questionnaire with closed questions from the Likert scale.As a result, the research pointed out that the main barriers are imposed by managers themselves, because without the encouragement and support the actions directed to the intrapreneur environment, the intrapreneurshipmay not thrive. The majority of respondents are female (81%), while only (19%) is of the male gender was also unable to verify that the organization is partly a culture geared to intrapreneurship.
Monografia
Keywords: Intraempreendedorismo; Colaboradores; Clínica médica.; Intrapreneurship; Employees; Medical Clinic; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO